Novel Optical-Node Architecture Utilizing Asymmetric-Multiport Wavelength-Selective Switches - Masaki Niwa; Yojiro Mori; Hiroshi Hasegawa; Ken-ichi Sato (IEEE Photonics Journal, 2016)
We propose a novel and highly scalable optical-node architecture utilizing MxN asymmetric-multiport wavelength-selective switches (WSSs), within which we implement subsystem-modular optical cross-connects (OXCs) and a transponder-bank-based add/drop part. Although the proposed add/drop part has a bank-based structure, it can realize flexible routing through the routing capability of the MxN WSSs. Numerical experiments verify that the proposed node architecture offers almost the same routing performance as the equivalent fully flexible node. Moreover, the proposed configuration attains substantial hardware reductions in terms of the number of WSS components in the OXC part, as well as that of optical amplifiers in the add/drop parts.